INFLUENCE OF BIOACTIVE SPICE EXTRACTS ON THE FUNCTIONAL AND MICROBIAL INTEGRITY OF A TRADITIONAL FERMENTED RICE FOOD : FERMENTED RICE FOOD - Masauda Muhammad Umar; Innocent Ojeba Musa; Miracle Uwa Livinus; Mustapha Abdulsalam; Tasnim Tasnim; Firdaus Fahdi; Amalia Riski Wahyulita (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
This study investigates the impact of incorporating natural spices ginger (Zingiber officinale), garlic (Allium sativum), and cloves (Syzygium aromaticum) at concentrations of 1%, 3%, and 5% on the microbial stability, physicochemical properties, nutritional composition, sensory attributes, and safety of Sinasir (Rice pancake), a traditional Nigerian fermented rice cake. Methods: Over an 8-week storage period, samples were analyzed for microbial load, pH, temperature, titratable acidity, proximate composition (carbohydrates, moisture, fat, ash, protein, and fiber), sensory evaluation, hazard analysis, and antimicrobial sensitivity. Results: this finding indicated that spice-treated samples, particularly those with 5% clove and garlic, exhibited significantly lower bacterial and coliform counts compared to the control, which reached TNTC by week 4. The 5% clove sample maintained bacterial counts below 3.6 × 10⁵ CFU/g at week 8. pH levels in spiced samples remained acidic (4.2–4.5), while the control increased to 5.8, correlating with spoilage. Moisture content decreased with higher spice concentrations, enhancing shelf stability. The 5% garlic sample showed the highest protein content (9.85%), and the 5% clove sample had the highest ash content (2.41%). Sensory evaluation favored 3% and 5% spice-treated samples. The bacterial isolates include Bacillus cereus, Pseudomonas aeruginosa, Enterobacter aerogenes, and Lactobacillus fermentum.   Antimicrobial assays revealed significant inhibition zones against foodborne pathogens, particularly for clove and garlic extracts. Conclusion: These findings support the use of local spices in improving the safety, quality, and acceptability of traditional fermented foods.